Chromium supplementation modulates glucose metabolism in heat-stressed Girolando dairy cows - Lilian dos Santos Ribeiro; Felipe Zandonadi Brandão; Luciano de Rezende Carvalheira; Diana Rangel de Lemos; Gustavo Torres de Souza; Ribrio Ivan Tavares Pereira Batista; Luiz Sérgio de Almeida Camargo; Bruno Campos de Carvalho (Semina: Ciências Agrárias, 2020)
The objective of this study was to evaluate the effects of dietary chromium supplementation on hepatic gene expression of lactating Girolando (Holstein x Gyr) cows under heat stress conditions in climatic chamber. Thirty-six ¾ Holstein x Gyr lactating cows were used, based on a 2x3 factorial scheme, to evaluate the effects of two diets (0 vs 0.50 mg of organic chromium kg-1 dry matter) and three environmental conditions (ECs): heat stress conditions in climatic chamber with ad libitum feeding (HS), a thermoneutral environment with ad libitum feeding (TN), and a pair-fed group in a thermoneutral environment (PF). Under HS group, the expression levels of glucose transporter 2 (GLUT2), glucose-6-phosphatase (G6Pase), and growth hormone receptor (rGH) were downregulated (P < 0.05) in chromium-supplemented cows compared to those in cows fed the control diet. GLUT2 expression was upregulated (P = 0.02) in the HS group and insulin-like growth factor 1 (IGF1) was downregulated (P < 0.01) in the PF group in cows fed the control diet compared to the expression in the TN group. No differences were observed between the ECs in terms of relative abundances of GLUT2, phosphoenolpyruvate carboxykinase (PEPCK), G6Pase, rGH, and IGF1 transcripts among the chromium-supplemented cows (P > 0.05). Heat stress caused changes in the expression of genes related to glucose metabolism, and organic chromium could modulate glucose metabolism in animals under heat stress conditions to some extent.